2013
DOI: 10.1186/1475-2891-12-1
|View full text |Cite
|
Sign up to set email alerts
|

Avocado consumption is associated with better diet quality and nutrient intake, and lower metabolic syndrome risk in US adults: results from the National Health and Nutrition Examination Survey (NHANES) 2001–2008

Abstract: BackgroundAvocados contain monounsaturated fatty acids (MUFA) dietary fiber, essential nutrients and phytochemicals. However, no epidemiologic data exist on their effects on diet quality, weight management and other metabolic disease risk factors. The objective of this research was to investigate the relationships between avocado consumption and overall diet quality, energy and nutrient intakes, physiological indicators of health, and risk of metabolic syndrome.MethodsAvocado consumption and nutrition data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
252
5
19

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(299 citation statements)
references
References 28 publications
(36 reference statements)
23
252
5
19
Order By: Relevance
“…In one study of corner stores in Philadelphia, the majority of available snack items were of low nutritional quality and those of lowest quality were pre-packaged (Lucan, S., Karpyn, A. et al, 2010). Reliance on prepackaged snacks may result in displacement of snacks that include fresh fruits and vegetables or whole grains (Smith, L., Ng, S. et al, 2013). However, some have suggested that recent increases in demand for prepackaged snacks might prompt industry to increase availability of more nutritious options.…”
Section: Discussionmentioning
confidence: 99%
“…In one study of corner stores in Philadelphia, the majority of available snack items were of low nutritional quality and those of lowest quality were pre-packaged (Lucan, S., Karpyn, A. et al, 2010). Reliance on prepackaged snacks may result in displacement of snacks that include fresh fruits and vegetables or whole grains (Smith, L., Ng, S. et al, 2013). However, some have suggested that recent increases in demand for prepackaged snacks might prompt industry to increase availability of more nutritious options.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, diets with high omega 3 polyunsaturated fatty acids are associated with decreased Aβ levels (Hjorth et al, 2013; Julien et al, 2010; Lebbadi et al, 2011; Zerbi et al, 2014), and one study found that a diet low in fat and high in oleic acid was able to reduce Aβ levels and pathology in transgenic mice (Amtul et al, 2010). In addition, the high sucrose and fructose contents of Western diets are also associated with cognitive impairment in humans (Francis and Stevenson, 2011) and increased Aβ (Lakhan and Kirchgessner, 2013; Moreira, 2013; Orr et al, 2014), and tau pathology (Orr et al, 2014) in rodents. Even in the absence of HFD, 10% sucrose water increased Aβ in a mouse model of AD (Cao et al, 2007), and a high fructose diet impaired spatial memory in rats (Ross et al, 2009).…”
Section: Obesity/metabolic Syndrome As Risk Factors For Admentioning
confidence: 99%
“…In this respect, avocados contain three of the most important ones, which are vitamins. Avocado fat consists predominantly of monounsaturated oleic acid, which has been found to reduce harmful lowdensity lipoprotein cholesterol, while maintaining beneficial highdensity lipoprotein cholesterol, and to perform better than typical lowfat diets (Bergh, 1992;Fulgoni et al, 2013). Although avocado is primarily consumed fresh, a substantial increase in the use of avocadobased products (e.g., guacamole) and oil for cosmetics and culinary purposes also suggest further market growth (Bost et al, 2013).…”
Section: Introductionmentioning
confidence: 99%